EVALUASI KEMAMPUAN PRODUKSI ALAT GALI-MUAT DAN ALAT ANGKUT GUNA MENCAPAI TARGET PRODUKSI BATUBARA 180.000 TON BULAN OKTOBER 2015 DI PIT LIMOA TAMBANG AIR LAYA EXTENTIONTIMUR PT BUKIT ASAM (PERSERO)TBK UPTE - Maria Jeane Inggrid; E.P.S.B Taman Tono; Janiar Pitulima (MINERAL, 2016)
Eastern Extension of Pit Air Laya Limoa Mine was one of Air Laya Mine site that has coal miningbusiness license owned by PT Bukit Asam (Persero) Tbk. Excavator and truck method were applied inthat mine site. Mechanical equipments used in this site were 1 unit of Komatsu PC 800 SE Excavatorand 6 units of HINO LM 500 Dump Truck. Coal production target in Eastern Extension of Pit Air LayaLimoa Mine in October 2015 was 180.000 ton, but the production capacity of load haul equipment was157.179,39 ton with the work time efficiency at 14,07 hour/day and load haul equipment productiononly 129.245,20 ton with the work time efficiency at 13,97 hour/day. Therefore, evaluation wasnecessary throughout factors affecting working performance of mechanical equipment to achieve thetarget. Evaluation in achieving the target of coal production was conducted by calculating theproductivity, work efficiency and match factor. The data required to obtain these values includedequipment cycle time, the effective work time effeciency, the amount of bucket loading, density andcoal swell factor. Then the data was processed by using formula of mechanical soil removal andanalyzed based on literature related to the issue. After the evaluation of factors affectingperformance of mechanical equipments then work time effeciency corrected to be 15,61 hours/dayand additional of 6 to 7 unit of conveyance. There were changes in work time effeciency between loadhaul equipments and conveyance from 0,83 to 0,97. Production capabilities generated load haulequipment after being evaluated was 192.291,14 tons and production capabilities of conveyances,after the evaluation amounted to 188.236,03 tons.